Effects of Cryopreservation on Cell Metabolic Activity and Function of Biofabricated Structures Laden with Osteoblasts - Hernández-Tapia, Laura G; Fohlerová, Zdenka; Žídek, Jan; Alvarez-Perez, Marco A; Čelko, Ladislav; Kaiser, Jozef; Montufar, Edgar B (Materials (Basel, Switzerland), 2020)
Biofabrication and maturation of bone constructs is a long-term task that requires a high degree of specialization. This specialization falls onto the hierarchy complexity of the bone tissue that limits the transfer of this technology to the clinic. This work studied the effects of the short-term cryopreservation on biofabricated osteoblast-containing structures, with the final aim to make them steadily available in biobanks. The biological responses studied include the osteoblast post-thawing metabolic activity and the recovery of the osteoblastic function of 3D-bioprinted osteoblastic structures and beta tricalcium phosphate (β-TCP) scaffolds infiltrated with osteoblasts encapsulated in a hydrogel. The obtained structures were cryopreserved at -80 °C for 7 days using dimethyl sulfoxide (DMSO) as cryoprotectant additive. After thawing the structures were cultured up to 14 days. The results revealed fundamental biological aspects for the successful cryopreservation of osteoblast constructs. In summary, immature osteoblasts take longer to recover than mature osteoblasts. The pre-cryopreservation culture period had an important effect on the metabolic activity and function maintain, faster recovering normal values when cryopreserved after longer-term culture (7 days). The use of β-TCP scaffolds further improved the osteoblast survival after cryopreservation, resulting in similar levels of alkaline phosphatase activity in comparison with the non-preserved structures. These results contribute to the understanding of the biology of cryopreserved osteoblast constructs, approaching biofabrication to the clinical practice.
Keywords: bioprinting; biofabrication; osteoblast; bone construct; cryopreservation; metabolic activity; ALP activity